Comparison of Motivation and Geography Learning Outcomes of Students Who Live in Islamic Boarding Schools and Outside Islamic Boarding Schools - Amiqoh, Lilis; Osman, Shuki; Yilmaz, Mustafa (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The purpose of this research is to determine whether or not there are differences in the motivation and learning outcomes of geography Madrasah Aliyah Nurul Jadid students who live in Islamic boarding schools and outside Islamic boarding schools. Methodology:This research uses comparative quantitative research. Data collection methods use observation, questionnaires and documentation. The population of this study was all students in classes X-XII Madrasah Aliyah Nurul Jadid, totaling 113 students. There are 78 students living in Islamic boarding schools and 35 students living outside Islamic boarding schools. Sampling used the Proportional Sampling technique. The number of samples in this study was 65 students who lived in Islamic boarding schools and 32 students who lived outside Islamic boarding schools. Analysis of hypothesis testing on learning motivation variables and student geography learning outcomes using Parametric Statistics with the Polled Variance t-test formula and Independent t test SPSS 23 for Windows program. Main Findings: The results of research data analysis show that there are differences in motivation to learn geography between students living in Islamic boarding schools and outside Islamic boarding schools. Likewise, with student learning outcomes, there are differences in motivation to learn geography between students who live in Islamic boarding schools and outside Islamic boarding schools. Novelty/Originality of this study: Comparing these aspects between students inside and outside Islamic boarding schools can reveal patterns of insight regarding the impact of the learning environment, motivation and teaching methodology on geography learning outcomes.